The Educational Philosophy among the Faculty Members at the Hashemite University - Al-Zyoud, Abd Alkhaliq (Journal of Educational and Psychological Sciences, 2020)
This study aims to determine the educational philosophy orientations of the faculty members at the Hashemite University. The educational philosophy orientations of faculty were examined using the quantitative research method, through the survey. A questionnaire was developed in order to identify the education philosophy orientations adopted by the faculty members, and results indicated that various philosophical orientations are held by the participants of the study from among the faculty members at the Hashemite University. Results showed that Reconstructionism was the educational philosophy adopted by a large percentage of the participants, followed by progressivism (m=4.17), Constructivism (m=4.15), Perennialism (m=4.10) and essentialism (m=3.67).
Keywords: Educational philosophy; Faculty members; Hashemite University